2005
DOI: 10.1097/01.rlu.0000156798.59230.2e
|View full text |Cite
|
Sign up to set email alerts
|

FDG Uptake in Brown Adipose Tissue Mimicking an Adrenal Metastasis: Source of False-Positive Interpretation

Abstract: Brown adipose tissue (BAT) uptake of F-18 fluorodeoxyglucose (FDG) poses a significant challenge to positron emission tomography interpretation. BAT is not only localized to the supraclavicular areas, but is also seen in the neck, mediastinum, axillae, costovertebral junctions, and retrocrural and periadrenal regions. We illustrate a case of typical supraclavicular BAT uptake in association with a discrete right adrenal region focus. On repeat study after diazepam administration, both the supraclavicular and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…There are some indications that brown adipose tissue activity is blocked by diazepam or other tranquilizers (6,60), and such treatment is recommended for "nervous" patients (35) [but not all find such effects (21), at least not experimental animals]. The nuclear medicine literature refers to previously observed diazepam-binding sites in brown adipose tissue as an explanation for this effect, but because brown adipose tissue is stimulated by the sympathetic nervous system and because anxiety may activate this system, it is possible that the inhibition of brown fat FDG uptake by diazepam is due to reduced sympathetic activity.…”
Section: Human Brown Adipose Tissue Activity Is Sympathetically Stimumentioning
confidence: 99%
“…There are some indications that brown adipose tissue activity is blocked by diazepam or other tranquilizers (6,60), and such treatment is recommended for "nervous" patients (35) [but not all find such effects (21), at least not experimental animals]. The nuclear medicine literature refers to previously observed diazepam-binding sites in brown adipose tissue as an explanation for this effect, but because brown adipose tissue is stimulated by the sympathetic nervous system and because anxiety may activate this system, it is possible that the inhibition of brown fat FDG uptake by diazepam is due to reduced sympathetic activity.…”
Section: Human Brown Adipose Tissue Activity Is Sympathetically Stimumentioning
confidence: 99%
“…A high glucose uptake of active BAT allows its detection in human patients undergoing 18 F-FDG PET/CT imaging and may at the same time interfere with diagnostic tumor detection (6,9,10,12).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, 3 independent studies finally reported the unequivocal interpretation of said signals as metabolically active BAT (3)(4)(5). In clinical practice, activated BAT disturbs diagnosis (6). Particularly in the context of tumor diagnosis, this is a not-tobe-underestimated problem (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Secondly, brown fat FDG uptake in the adrenal region can mimic adrenal uptake and was previously described (14,15). However, review of the FDG PET/CT scans was not hampered by brown fat.…”
Section: Discussionmentioning
confidence: 99%